Comparison of low level of pregnancy-associated plasma protein - A between first and early second trimester of pregnancy in intrauterine growth restriction - Susan, Zobaida Sultana; Bulbul, Surayea; Shilpi, Khadija Rahman; Nayeem, Abu; Pervin, Sayeeda; Purabi, Ayesha Siddika; Rouf, Salma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Intrauterine growth restriction (IUGR) is the failure of the fetus to reach its growth potential due to pathological factors, most commonly placental dysfunction and is a major contributor to perinatal morbidity and mortality worldwide. This study compares low maternal serum PAPP-A levels in the first and early second trimesters to predict IUGR risk. The aim of the study was to compare low levels of Pregnancy-Associated Plasma Protein-A (PAPP-A) between the first and early second trimesters of pregnancy in relation IUGR. Methods: This prospective cohort study was conducted at the Department of Obstetrics and Gynecology, Dhaka Medical College Hospital in 2020, including 186 pregnant women (6–12 and 13–20 weeks gestation) to assess PAPP-A’s predictive value for IUGR. Eligible healthy singleton pregnancies underwent blood PAPP-A testing and serial ultrasounds with Doppler. IUGR was diagnosed by fetal measurements and Doppler, with low PAPP-A defined as <0.5 MoM. Data analysis used SPSS with ROC curves. Results: Most participants were aged 26–29 years. IUGR occurred in 17 (Group A) and 19 (Group B), with low PAPP-A in 12 and 13 cases, respectively. Low PAPP-A significantly predicted IUGR (RR: 10.73 and 9.03, p<0.001). Diagnostic performance was high in both trimesters (AUC>0.85, sensitivity>89%, specificity>69%). Serum PAPP-A is a reliable early predictor of IUGR. Conclusions: Low maternal serum PAPP-A levels in early pregnancy moderately predict IUGR, with comparable accuracy in both first and early second trimesters.